Peptidoglycan-Binding Anchor Is a Pseudomonas aeruginosa OmpA Family Lipoprotein With Importance for Outer Membrane Vesicles, Biofilms, and the Periplasmic Shape - Paulsson, Magnus; Kragh, Kasper Nørskov; Su, Yu-Ching; Sandblad, Linda; Singh, Birendra; Bjarnsholt, Thomas; Riesbeck, Kristian (Frontiers in Microbiology, 2021)
The outer membrane protein A (OmpA) family contains an evolutionary conserved domain that links the outer membrane in Gram-negative bacteria to the semi-rigid peptidoglycan (PG) layer. The clinically significant pathogen Pseudomonas aeruginosa carries several OmpA-family proteins (OprF, OprL, PA0833 and PA1048) that share the PG-binding domain. These proteins are important for cell morphology, membrane stability, biofilm and outer membrane vesicle (OMV) formation. In addition to other OmpAs, in silico analysis revealed that the putative outer membrane protein (OMP) with gene locus PA1041 is a lipoprotein with an OmpA-domain, and hence is a potential virulence factor. This study aims to evaluate PA1041 as a PG-binding protein and describe its effect on the phenotype. Clinical strains were confirmed to contain the lipoprotein resulting from PA1041-expression with western blot, and PG binding was verified in ELISA. By using a Sepharose bead-based ELISA, we found that the lipoprotein binds to mDAP, an amino acid in the pentapeptide portion of PGs. The reference strain PAO1 and the corresponding transposon mutant PW2884 devoid of the lipoprotein were examined for phenotypic changes. Transmission electron microscopy revealed enlarged periplasm spaces near the cellular poles in the mutant. In addition, we observed an increased release of OMV in TEM-pictures, which could be confirmed by nanoparticle tracking analysis. Importantly, mutants without the lipoprotein produced a thick, but loose and unorganized biofilm in flow cells. In conclusion, the lipoprotein from gene locus PA1041 tethers the outer membrane to the PG layer, and mutants are viable, but display severe phenotypic changes including disordered biofilm formation. Based upon the phenotype of the P. aeruginosa PW2884 mutant and function of the protein we designate the lipoprotein with locus tag PA1041 as "Peptidoglycan binding anchor" (Pba).